Method for Analysis of the Effect of Geomagnetic Disturbances on Ultraviolet Airglow Intensity. Issue 11 (19th November 2018) - Putis, M.; Bobik, P.; Mackovjak, S.
Abstract : Airglow is a dynamic phenomenon which depends on the geographical location, season, local time, geomagnetic activity, and other conditions. Variations in UV nighttime airglow (300–500 nm) caused by magnetospheric disturbances for several selected points around globe are presented in this study. Used airglow intensity data were evaluated in empirical model Atmospheric Ultraviolet Radiance Integrated Code. We focus on points around the auroral oval position for very disturbed magnetosphere ( K p = 8) and positions chosen for the Airglow MONitor network. This network will consist of a set of small one pixel detectors, designed for long time measurements. A simple statistical method was developed for long time data analysis of geomagnetic disturbances of airglow. Results of the method for planned stations are presented. Key Point: Review of UV airglow response to geomagnetic disturbances for several selected points around globe